Application of triple correlation and bispectrum for interference immunity improvement in telecommunications systems - Molchanov, Pavel; Totsky, Alexandr (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a new noise immunity encoding/decoding technique by using the features of triple correlation and bispectrum widely employed in digital signal processing systems operating in noise environments. The triple correlation- and bispectrum-based encoding/decoding algorithm is tested for a digital radio telecommunications binary frequency shift keying system.
Keywords: telecommunications; frequency shift keying; redundant encoding; triple correlation; bispectrum